Short-chain grafting of tetrahydrofuran and 1,4-dioxane cycles on vinylchloride-maleic anhydride copolymer (eXPRESS Polymer Letters)
Mass increase of vinylchloride-maleic anhydride (VC-MA) copolymer samples aged in tetrahydrofuran (THF) or in 1,4-dioxane results from chemical interaction of VC-MA macromolecules with 1,4-dioxane or THF. Microstructure of the products of such modification was proved by infrared spectroscopy (IR-) and nuclear magnetic resonance spectroscopy (13C NMR and 1H NMR). Mechanism of modification has been proposed. The results of microstructure research of VC-MA samples aged in THF and in 1,4-dioxane coincide with already known data on the reactions of opening of these and other oxygen-containing cycles under mild conditions.